ON NECESSITY OF DEVELOPMENT OF ECOLOGICAL BINDING MATERIALS AND BLENDS ON THEIR BASIS - S. P. Dingilevskiy; Yu. Yu. Guminskiy (Литьë и металлургия)
The issue of environmental problems of the modern foundry production is touched upon in this article. The types of environmentally dangerous substance and their influence on human organism are considered in it. The ways of solution of these problems are offered.